Family factors supporting childhood education in disadvantaged environments: opportunities for educational achievement - Formoso-Silva, María; Varela-Crespo, Laura; Caballo-Villar, María Belén (Revista Complutense de Educación, 2025)
The relationship between poverty and education is particularly complex, influenced by multiple factors that impoverish essential dimensions of children's daily lives. The aim of the article is to analyse the family factors that provide support for promoting the academic success of children and adolescents from vulnerable socio-economic backgrounds, specifically: the importance families attach to education, their expectations regarding their children's education, the educational support they provide, and their participation in the school context. The qualitative research was carried out through in-depth semi-structured interviews with an intentional sample of 15 families (parents) facing poverty and/or social vulnerability, who had children of minor age. Data analysis, supported by the ATLAS.ti 8 programme, was carried out using a content analysis strategy based on two coding cycles, resulting in a total of 18 categories, from which two were selected for this paper: 1) the importance of education and educational expectations, and 2) school participation and family involvement. The results highlight that family factors supporting academic success are constrained by conditions of poverty (material, educational…) that reduce educational opportunities and widen inequalities. It is concluding that there is a need to move towards educational equity proposals that strengthen the support provided by families and community network, to the reduce the educational gap among the most vulnerable children.
Keywords: family; poverty; childhood; school; equity